can any one help me with my assign?
f(x) = 2x - 3
3x + 4
$\displaystyle f(x)=\frac{2x-3}{3x+4}$
write it like this
$\displaystyle f(x)=(2x-3)(3x+4)^{-1}$ use product rule
product rule in general
$\displaystyle H(x)=A(x)B(x) \Rightarrow H'(x)=A'(x)B(x)+B'(x)A(x)$ or leave it as the first form and use division rule
division rule in general
$\displaystyle H(x)=\frac{A(x)}{B(x)} \Rightarrow H'(x)=\frac{B(x)A'(x)-B'(x)A(x)}{(B(x))^2}$
you should try show us your answer and if there is any wrong I will correct it